SOCIAL MEDIA ADVERTISING AND EVENT MARKETING'S INFLUENCE ON BRAND AWARENESS AND PURCHASE INTENTIONS - Wandi Kurniadi; Edhie Budi Setiawan; Dian Artanti Arubusman (SEAN Institute, 2022)
The purpose of this study was to determine the relationship and influence between Social Media Advertising and Event Marketing on Brand Awareness and its impact on Tenue de Attire's Purchase Intention products. The population in this study were people who followed the official Tenue de Attire account on Instagram. This study uses Path Analysis to measure the relationship and the influence of independent variables with dependent variables. In this study, data was obtained by collecting questionnaires to the population through Direct Messages. The results obtained in this study are, Social Media Advertising and Event Marketing have a significant influence on Brand Awareness and its impact on Tenue de Attire's Purchase Intention products.